Medical Imaging 2021: Computer-Aided Diagnosis 2021
DOI: 10.1117/12.2582039
|View full text |Cite
|
Sign up to set email alerts
|

Classification of schizophrenia from functional MRI using large-scale extended Granger causality

Abstract: The literature manifests that schizophrenia is associated with alterations in brain network connectivity. We investigate whether large-scale Extended Granger Causality (lsXGC) can capture such alterations using restingstate fMRI data. Our method utilizes dimension reduction combined with the augmentation of source time-series in a predictive time-series model for estimating directed causal relationships among fMRI time-series. The lsXGC is a multivariate approach since it identifies the relationship of the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…This paper investigates a novel method, large-scale Extended Granger Causality (lsXGC), for discovering relations in high-dimensional dynamical systems involving observational data. The lsXGC method addresses the Ground truth Figure 2: Performance of various algorithms, namely mutual information (MI) [9], transfer entropy (TE) [8], multivariate Granger causality (GC) [16], and our proposed method (lsXGC, [2]) on the Netsim dataset [90]. As can be seen, the proposed algorithm (lsXGC) significantly outperforms other methods from the literature, suggesting robustness of the method against noise and hemodynamic response effects encountered in fMRI data.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This paper investigates a novel method, large-scale Extended Granger Causality (lsXGC), for discovering relations in high-dimensional dynamical systems involving observational data. The lsXGC method addresses the Ground truth Figure 2: Performance of various algorithms, namely mutual information (MI) [9], transfer entropy (TE) [8], multivariate Granger causality (GC) [16], and our proposed method (lsXGC, [2]) on the Netsim dataset [90]. As can be seen, the proposed algorithm (lsXGC) significantly outperforms other methods from the literature, suggesting robustness of the method against noise and hemodynamic response effects encountered in fMRI data.…”
Section: Discussionmentioning
confidence: 86%
“…For studying the underlying pathophysiology of neurological and psychiatric disease, functional connectivity among various cortical regions has been identified as an important research subject [1]. By providing images with sufficiently high spatial resolution and the hemodynamic response dynamics over a temporal axis, fMRI studies have demonstrated a tremendous potential to serve as a biomarker for neurologic and psychiatric disease [2][3][4][5]. Currently, most of the diagnosis in brain-related disorders relies on clinical symptom evaluations, such as based on neuropsychological testing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations